Phytosynthesis of silver nanoparticles by semecarpus anacardium L. leaf extract - Raju, D.; Hazra, Sulekha; Mehta, Urmil J. (Materials Letters, 2013)
Green synthesis of silver nanoparticles (AgNPs) using Semecmpus anacardium L leaf extract was studied. The reduction of silver (Ag+) ions was characterized by using UV-vis spectrophotometer showing formation of AgNPs within 15-20 mm. A time dependent reaction showed the increase in the nanoparticles (NPs) with time. Transmission electron microscopy (TEM) analysis showed that the synthesized AgNPs varied from 10 to 25 nm and has spherical shape. The Fourier transform infrared (FTIR) analysis showed that phenols and protein were responsible for the formation of the AgNPs. The energy dispersive spectroscopy (EDAX) analysis confirms the formed NPs were of silver. The quantification of AgNPs was studied by inductive coupled plasma spectrometry (ICP-AES). The important outcome of this work can be value addition to the medicinal plants in synthesis of NPs for biomedical applications. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: FTIR; Leaf extract; Nanoparticles; Semecarpus anacardium; synthesis; TEM